Innovation First and Foremost: The Case of Oman’s Ranking in the Global Innovation Index - Alkhanjari, Almutasim (Advances in Social Sciences Research Journal, 2021)
One of the most important reports that evaluate the degree of innovation in countries is the Global Innovation Index (GII). Oman’s score has been exceptional from 2013, with experts anticipating it to ascend to the first 40 nations in GII; nevertheless, over the previous two years, the ranking of the country has significantly dropped to 80 in 2019 and is expected to remain to decline after being 57 in 2018. The study’s objective is to determine the factors that led to the Oman decline in GII, analyze the involvement of public institutions in this drop in terms of policy change or reform, and explore the societal impact of this drop. Because of a lack of data on the subject, this exploratory, descriptive research used a combination of data collection methods, involving an interview with five specialists and a circulation of 204 survey questionnaires. To achieve uniformity and relevancy, participants were chosen based on the study’s themes. This research focused on identifying the factors contributing to the sudden decline in the GII compared to prior years. Additionally, it layout a framework for key stakeholders to execute the major adjustments required to enhance performance in crucial innovation indicators. Finally, it will result in increasing professional and organizational awareness of policy instrumentation in Oman and will offer avenues for future research on this topic and governmental policies that will enhance several of the GII indicators, notwithstanding Oman’s drop in ranking.